Control of charge of supercapacitor’s battery as device with diffusion properties - Busher, Victor (Publishing House of Lviv Polytechnic National University, 2012)
There has been analyzed the charge processes in a battery of series-connected supercapacitors and developed the fractional differentialaperiodic regulator for a model of fractionally-integrated section for SIMULINK with high accuracy and fast performance at the fixed calculation step. The proposed model is an improved version of the supercapacitor that takes into consideration the diffusive processes and parameters’ variation on change of the current polarity. Проведено аналіз процесу заряджання батареї, що складається з послідовно злучених суперконденсаторів, та розроблено для SIMULINK дробовий диференційно-аперіодичний регулятор високого ступеня точності та швидкодії з фіксованим кроком для моделі дробово-інтегрованої секції. Запропонована покращена модель суперконденсатора, що враховує дифузійні процеси та зміну параметрів внаслідок зміни полярності струму.
Керування процесом заряджання батареї суперконденсаторів як присторою з дифузійними властивостями
Keywords: control; supercapacitor’s battery